2011
DOI: 10.1002/asi.21573
|View full text |Cite
|
Sign up to set email alerts
|

Situated topic complexity in interactive video retrieval

Abstract: The overarching goal of this study is to place additional emphasis on the ability to observe, extend, and apply findings across different experimental studies and/or digital projects by providing further insight into some of the broader processes within interactive (user-centered) video retrieval. The variable at the center of this particular investigation included a user-centered definition of topic complexity, or "situated topic complexity," where its influence on other factors within the interactive video p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Hence, features should be designed to enhance and complement the natural language search bar. This was aligned with evidence found in the literature review where the query formulation is user-centric and had the most potential for advancing interfaces and features (Albertson & Meadows, 2011). The quality of the results list through this method is highly dependent on the query formulation.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Hence, features should be designed to enhance and complement the natural language search bar. This was aligned with evidence found in the literature review where the query formulation is user-centric and had the most potential for advancing interfaces and features (Albertson & Meadows, 2011). The quality of the results list through this method is highly dependent on the query formulation.…”
Section: Discussionsupporting
confidence: 81%
“…The words used in the search query provided separation between relevant and nonrelevant resources. Albertson and Meadows (2011) argued that keyword search would remain the most preferred input search feature, even for complex search tasks. The simplicity of the query by keywords afforded both trained and untrained users to handle searches.…”
Section: Expressing Information Needs and Navigation Of Search Domainmentioning
confidence: 99%
“…A post-search questionnaire, partially derived from the 2004 TREC Interactive Track and common to other interactive information retrieval studies [1, 4, 22], was used to collect data from the users. The questionnaire asked users to rate:…”
Section: Methodology and Systemmentioning
confidence: 99%
“…A sub-question arising from this particular examination included the association between feedback and user satisfaction throughout search topics with varying durations and user actions. Furthermore, it has previously been shown that increases or decrease in the difficulty of a search topics and thus the duration of video searches will affect user opinions about the search session and/or supportiveness of an experimental video retrieval system [4]. Applying this premise for the purposes of this study led to the exploration of whether different levels of user satisfaction can be an indicator of more or less feedback contributed or requested during video searches.…”
Section: Research Questionsmentioning
confidence: 95%
“…In addition the use, impact and perceptions of specific interface features and designs of video surrogates, which enable assessment of video content by users, including slideshows, storyboards and fast forwards (Wildemuth et al, 2003) have been directly examined across studies employing different situations and/or contextual factors steered by basic usability metrics (Albertson, 2010b;Albertson and Meadows III, 2011).…”
mentioning
confidence: 99%